Prevalence, patterns, and determinants of gender-based violence among women and girls in IDP camps, Mogadishu-Somalia - Hassan Abdullahi Dahie; Mohamed Maalim Dakane; Bashir Said Hassan (Elsevier, 2023)
Background: Gender-based violence (GBV) against women and girls, is a global pandemic that affects 1 in 3 women in their lifetime. Somalia is one of the leading countries in human rights violations and has one of the highest rates of sexual and gender-based violence (SGBV) worldwide. Such violence is more prevalent among women and girls in internally displaced persons (IDP) camps who lack livelihood and civil protections. Therefore, this study was designed to identify the prevalence and the determinants of gender-based violence in IDP camps in Deynile district, Somalia. Methods: This is a cross-sectional study design conducted in IDP camps in Deynile District from August 1 to September 30, 2022. A total of three hundred eighty-four women and girls aged 18 years and above living in the selected IDP camps were involved in the study. The camps were selected randomly while households and participants were selected systematic random sampling. The recall period was set at 12 months (August 2021 to July 2022). Participants were interviewed by well-trained research assistants using pre-tested structured questionnaire. Data was entered into and analyzed with SPSS 25.0. Logistic regression was used, and the significance level was set at p value ≤ 0.05. Result: The study revealed that gender-based violence was quite common in the IDP camps in Mogadishu's Deynile area. Physical abuse was the most prevalent type of GBV, which was primarily committed by intimate partners, parents, and other family members. The main factors associated with gender-based violence were young age (OR=4.77, 95% CI: 1.96-11.63, p<0.001), extended family structure (OR=7.89, 95% CI: 4.30-14.47, p<0.001), household size >5 individuals (OR=1.86, 95% CI:1.04-3.30, p<0.005), employment (OR=1.57, 95% CI: 1.0.41-2.32, p<0.05), substance misuse (OR=3.25, 95% CI: 1.57-6.73, p<0.05), a long distance to the nearest police station (OR=2.75, 95% CI:1.51-5.00, p<0.005), and camp safety protection (OR=1.94, 95% CI:1.24-3.30, p<0.005). Conclusion and recommendations: There was a high prevalence of gender-based violence in the IDP camps in Mogadishu's Deynile area. The most common form of GBV was physical violence mainly perpetuated by intimate partners. The study recommends improving some of the modifiable factors that were strongly associated with gender-based violence.